Case study of community action for rural development - Nicolas, Eleanor E. (2001)
The inadequacy and inability of the government in providing the needs of the indigenous communities led to the formation of the Community Action for Rural Development (CARD). CARD utilized programs that primarily support the rights of the indigenous peoples (IPs) to ancestral domain, pursuit of advocacy, economic and political empowerment. This case study intends to help CARD execute its social development agenda among tribal communities of Kapalong, Davao del Norte. It addresses how CARD carries out its advocacy work, what issues have been advocated, what factors facilitated or hindered its advocacy work, what are its capability needs, and how can its advocacy work be enhanced or strengthened. Thus, CARD staff members signified their need to have continuous training on advocacy. There might be innovations, new trends and ways of doing and managing the programs they need to learn and apply in their work.
Keywords: Social advocacy; Nongovernmental organizations -- Case studies; Rural development -- Kapalong (Davao del Norte); Community Action for Rural Development (CARD); Indigenous peoples -- Kapalong (Davao del Norte)